Causes of Death in Patients with Severe Aortic Stenosis: An Observational study. Issue 1 (December 2017) - Minamino-Muta, Eri; Kato, Takao; Morimoto, Takeshi; Taniguchi, Tomohiko; Shiomi, Hiroki; Nakatsuma, Kenji; Shirai, Shinichi; Ando, Kenji; Kanamori, Norio; Murata, Koichiro; Kitai, Takeshi; Kawase, Yuichi; et al.
Abstract Whether patients with severe aortic stenosis (AS) die because of AS-related causes is an important issue for the management of these patients. We used data from CURRENT AS registry, a Japanese multicenter registry, to assess the causes of death in severe AS patients and to identify the factors associated with non-cardiac mortality. We enrolled 3815 consecutive patients with a median follow-up of 1176 days; the 1449 overall deaths comprised 802 (55.3%) from cardiac and 647 (44.7%) from non-cardiac causes. Heart failure (HF) (25.7%) and sudden death (13.0%) caused the most cardiac deaths, whereas infection (13.0%) and malignancy (11.1%) were the main non-cardiac causes. According to treatment strategies, infection was the most common cause of non-cardiac death, followed by malignancy, in both the initial aortic valve replacement (AVR) cohort (N = 1197), and the conservative management cohort (N = 2618). Both non-cardiac factors (age, male, body mass index <22, diabetes, prior history of stroke, dialysis, anemia, and malignancy) and cardiac factors (atrial fibrillation, ejection fraction <68%, and the initial AVR strategy) were associated with non-cardiac death. These findings highlight the importance of close monitoring of non-cardiac comorbidities, as well as HF and sudden death, to improve the mortality rate of severe AS patients.